A novel subtype classification for acute intracranial atherosclerotic disease-related occlusion - Gan, Shujuan; Yi, Tingyu; Wu, Meihua; Huang, Weifeng; Sui, Yi; Wu, Yanmin; Liu, Shuyi; Miao, Zhongrong; Chen, Wenhuo (Frontiers in Neurology, 2025)
Background and purposedThe optimal endovascular therapy (EVT) strategy for intracranial atherosclerotic disease (ICAD)-related occlusion remains uncertain and may be influenced by its underlying pathogenesis. To address this, a novel classification system named Thrombus-Stenosis (TS) has been proposed. Our study aimed to assess the feasibility of the TS classification and its utility in guiding EVT strategy-making.MethodsICAD was defined as a significant fixed focal stenosis at the site of occlusion evidenced by final angiography or during endovascular treatment. The TS subtype was classified based on presence of the thrombus and stenosis degree of culprit artery with three categories, TS-type I (<70% stenosis with definite thrombus), TS-type II (≥70% stenosis with definite thrombus) and TS-type III (≥70%stenosis without definite thrombus). Four independent raters used the TS classification system to subtype the included cases. Interobserver reliability was assessed using the kappa (κ) coefficient. Differences in EVT strategies between the three TS groups were compared.ResultsA total of 105 definite ICAD-related occlusion cases were included and successfully classified into the three TS subtypes by the four independent raters, with high interobserver agreement (κ = 0.95): 33 patients with TS-type I, 46 with TS-type II, and 26 with TS-type III. Compared with TS-type I, the likelihood of performing emergent angioplasty was 44 times higher in TS-type III (95% CI, 5.1–369.8, p = 0.001) and 9 times higher in TS-type II (95% CI, 1.1–73.3, p = 0.047).ConclusionThe TS classification system is feasible for subtyping ICAD-related occlusions and is closely associated with EVT strategy-making.